Educa????o financeira de estudantes universit??rios: uma an??lise dos fatores de influ??ncia - Donadio, Rosimara (2014)
This study investigated the level of financial literacy of Brazilian university students and its possible relationship with social capital, perceived self-efficacy, consideration of future consequences and financial stress. The sample included students enrolled in a private University in Sao Paulo. These students come from different backgrounds, in terms of geographical origin, race, gender, age, marital status, socio-economic class, and family income. A factor analysis and a hierarchical regression were conducted. The factor analysis on the scales of financial self-efficacy, consideration of future consequences, and financial stress indicated that these instruments are appropriate for use with the sample college students. The findings revealed that some components of social capital, such as the level of father's education and the number of courses taken in finance have positive relation with the level of financial literacy of college students. The family income level and maternal education were not relevant. As for the other variables studied, the perceived self-efficacy was not related to the level of financial education, however, consideration of future consequences and financial stress could be related to the level of financial education of social subjects. The research question, the general and specific objectives, as well as the assumptions defined in the study were, respectively, answered, achieved and confirmed.